Pengaruh Literasi Keuangan dan Self-Efficacy Terhadap Perilaku Keuangan - Anastasia Anggarkusuma Arofah; Rani Kurniawati (Perwira Journal of Economics & Business, 2021)
Abstract Financial behavior has an important role for individuals, because it relates to the individual's ability to achieve predetermined goals. In managing finances, a person needs more than just financial literacy but must have confidence in his abilities. This attribute is known in the psychological literature as "self-efficacy". Using the survey on 150 senior high school students in Purbalingga Regency, financial literacy and self-efficacy being factor in affecting financial behavior. The result of research shows that financial literacy has a positive and significant contribution to financial behavior since the original sample value of 0.224 and the t-value of 2.420> 1.96. Self-efficacy has a positive and significant contribution to financial behavior with an original sample value of 0.256 and a t-value of 3.251> 1.96. Students with high financial literacy have good financial behavior, and students with high self-efficacy will be better in managing their personal finances.